Partial information about contagion risk, self-exciting processes and portfolio optimization - Nicole Branger; Holger Kraft; Christoph Meinerding (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
This paper compares two classes of models that allow for additional channels of correlation between asset returns: regime switching models with jumps and models with contagious jumps. Both classes of models involve a hidden Markov chain that captures good and bad economic states. The distinctive feature of a model with contagious jumps is that large negative returns and unobservable transitions of the economy into a bad state can occur simultaneously. We show that in this framework the filtered loss intensities have dynamics similar to self-exciting processes. Besides, we study the impact of unobservable contagious jumps on optimal portfolio strategies and filtering.
urn:nbn:de:hebis:30:3-315514
Keywords: G01; G11; 330; Asset Allocation; Contagion; Nonlinear Filtering; Hidden State; Selfexciting Processes